Association between bisoprolol plasma concentration and worsening of heart failure: (CVI ARO 6). Issue 2 (April 2020) - Arita, Takuto; Suzuki, Shinya; Kato, Yuko; Kano, Hiroto; Yajima, Junji; Matsuno, Shunsuke; Otsuka, Takayuki; Semba, Hiroaki; Uejima, Tokuhisa; Oikawa, Yuji; Nagashima, Kazuyuki; Yagi, Naoharu; et al.
Abstract: Background: Although bisoprolol has been established to prevent heart failure (HF), finding the optimal dose remains a challenge. It is crucial to understand the distribution of bisoprolol plasma concentration (Bis-PC) and association with outcomes. Methods: This was a single-center observational study in 114 HF patients under once-daily bisoprolol. After obtaining trough Bis-PC, patients were followed-up for 1 year. The primary endpoint was worsening of HF. Patients were divided according to the tertiles of Bis-PC. Results: In multivariate logistic regression analysis, independent predictors of high Bis-PC (1st tertile: ≥ 5.38 ng/mL) were age, eGFR, and bisoprolol dose. The cumulative incidence rates of the primary endpoint were 10.5%/13.2%/26.3% in low/middle/high Bis-PC categories, respectively (log rank test, p = 0.087). Bis-PC was independently associated with the primary endpoint (hazard ratio [HR], 1.19 [per ng/mL], 95% CI 1.03–1.36). In subgroups, high Bis-PC was independently associated with the primary endpoint in elderly (HR 6.32, 95% CI 1.34–29.83) and HF with preserved ejection fraction (HFpEF) (HR 3.52, 95% CI 1.06–11.70). Conclusions: Bis-PC was increased by age and renal dysfunction, and high Bis-PC was associated with worsening of HF in elderly and HFpEF patients. Care should be taken to avoid overdose. Graphical abstract: Image 1